Application program development on arm-based evaluation board - Chan, Wilson Wei Cheng (2015)
The objectives of the Final Year Project (FYP) include exploring the capabilities and characteristics of the ARM-based Cortex™-M3 microcontroller STM32F103ZG and the Keil MCBSTM32EXL evaluation board. The evaluation board enables the generation and testing of embedded application programs based on the STMicroelectronics STM32F103ZE/ZG ARM 32-bit Cortex™-M3 microcontroller. Through extensive research, applications have been devised using the Keil MDKARM software development tools. The temperature monitoring system and enhancement of the ‘ponglet’ game have been developed for the project. The report aims to present a comprehensive review of the applications development of the Final Year Project. In addition, a literature review has been done on the ARM-Based microcontroller and in particular, ARM® Cortex®-M3 processor core which resides within. Furthermore, the report provides a summary of the hardware and software components which have been used and the recommended improvements or modifications of the said applications for future work.